The Impact of Product Quality and Price on Buying ERSPO Jerseys for the Indonesian National Team in Surabaya - Kurniawan, Bima; Cordelia Izaak, Wilma (Publikasi Inspirasi Indonesia, 2026)
This study aims to analyze the effect of product quality and price on purchasing decisions of Erspo Indonesian National Football Team jerseys in Surabaya. The background is rooted in the rising enthusiasm of Indonesian football fans and the emergence of Erspo as an official national team apparel brand, which faced opportunities as well as criticism concerning product quality and pricing. The research employed a quantitative approach using purposive sampling with 108 respondents. Data collection was conducted through questionnaires using a Likert scale, and data analysis utilized the Partial Least Square (PLS) method. The findings indicate that both product quality and price have a positive and significant effect on purchasing decisions. This study contributes to the literature on consumer behavior in the sports apparel market and provides practical insights for local brands to strengthen their competitivene